2013
DOI: 10.1002/cjce.21860
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of petrologic end members of oil sands from the athabasca region, Alberta, Canada

Abstract: The aim of this study was to perform mineral and chemical characterisation of the four petrologic end members of Alberta oil sands in order to better understand the mineralogical and geochemical factors affecting bitumen extraction. X‐ray diffraction (XRD) results revealed that the petrologic end members contain a variable amount of quartz, clay minerals, carbonates, K‐feldspar, TiO2 minerals and pyrite and the Fe‐containing phases were also observed in Mössbauer spectra. Scanning electron microscopy‐energy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 49 publications
8
21
0
Order By: Relevance
“…The highest standard deviation of the water content was found for the MC supernatant at 1 min (±0.016 %), which could be related to the heterogeneous nature of this end member. This conjecture is consistent with previously published papers …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The highest standard deviation of the water content was found for the MC supernatant at 1 min (±0.016 %), which could be related to the heterogeneous nature of this end member. This conjecture is consistent with previously published papers …”
Section: Discussionsupporting
confidence: 94%
“…The shoulder near 420 °C was attributed to the low amount of siderite in the SFS of ES‐1, 7.5, and 15 min. The band attributed to the siderite mineral at 420 °C was reported by Osacky et al and Patterson et al, who identified carbonates in oil sands and coal ores, respectively . The band near 710 °C present in MC‐1, 7.5, and 15 min was mainly due to the thermal decomposition of carbonates (i.e., calcite, dolomite, and siderite).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations